Civil War heavy explosive ordnance : a guide to large artillery projectiles, torpedoes, and mines - Bell, Jack, 1941- (University of North Texas Press, 2003)
Covering 360 projectiles from public and private collections, this book is a reference for both Union and Confederate large calibre artillery projectiles, torpedoes and mines. Each data sheet shows multiple views of the projectile, diameter, weight, gun used to fire it and provenance.